Recuperación y difusión de un patrimonio: el Fondo del Exilio del Instituto Cervantes de Toulouse - Javier Campillo Galmés (Cahiers de Civilisation Espagnole Contemporaine)
The article adresses the constitution and development of the Exile collection of the library of the Instituto Cervantes of Toulouse from its inauguration in 1996 to the present day. The historical and demographic ties that have linked the city of Toulouse with Spain, markedly accentuated since the Republican exodus of 1939, are mentioned. The most interesting sections that make up the Exile collection are reviewed, with special attention to the publications of the Librairie des Éditions Espagnoles de Toulouse, to its literary collection La Novela Española, as well as to the different collections of short novels and the main titles of periodicals of the republican exile in France preserved in the library.